Depression in Adolescents with Graves’ Disease: A Review - Yunias Setiawati; Febria Rike Erliana (Journal of Clinical and Cultural Psychiatry, 2023)
Graves' disease is a form of autoimmune hyperthyroidism that accounts for 60-80% of all forms of hyperthyroidism in children and adolescents and occurs in >95% of cases of hyperthyroidism at all ages. In the entire pediatric population in America, this disease occurs with a prevalence of 1:10,000, while in adults it is 1:1000. This article aims to provide an overview about depression in adolescents with Grave’s disease. Chronic disease conditions such as the hormonal abnormalities of Graves' disease in adolescence can affect the stage of adolescent biopsychosocial development. Adolescents with chronic diseases who undergo treatment for a long period of time can significantly limit the lives of adolescents and have an impact on adolescent mental health, including anxiety and depression, low self-esteem, poor social and family relationships and academics. Graves' disease and depression are believed to be related because hormones affect the brain and body. Some studies estimate that about 69% of people diagnosed with hyperthyroidism are depressed. Depression in adolescents with Graves’ disease can be managed by psychopharmaceutical including tricyclic antidepressants, SSRI, SNRI, and various psychotherapy. Parental and peer support are very important to improve the outcomes.